Real estate management: what boundaries? A European approach. (1st January 2014) - Abatecola, Gianpaolo; Cafferata, Roberto
Real estate has always played a key role in the economy of industrialised countries. To date, fine-tuned studies have started to grow and develop to inform about the evolution of real estate management as a per se discipline for education, research and practice. Increasing reviews have also systematised what is hot and what is not in terms of research trends within this field. However, what seems to remain largely unaddressed is the appropriate conceptual and methodological classification of the boundaries delimiting the field itself. We do believe that this gap is not minor for both the research and practice, in that it negatively affects the possibility of conducting appropriate analyses from both qualitative and quantitative perspectives. We have thus conceived this article as an intended contribution to filling the stated gap.